Open-Source Web System to Improve Eating Styles Accompanied by Exercises: HealthLife - Miranda, Alba; Carreño S.; Vera J. (My University, 2023)
Nowadays, dietary and physical health is as important as general health problems. Several web and mobile applications try to cover health care to provide better food and physical conditions for users, but approximately 90% of these are paid. The objective of this research was to develop HealthLife. This open-source web system makes it easier for users to obtain meal and exercise plans, complemented with the help of professionals in each of these areas. The methodology was divided into two parts: on the one hand, a Systematic Mapping Study (SMS) was used for the bibliographic study; on the other hand, a novel software development methodology called OSCRUM was used to carry out the development tasks in an orderly and rigorous manner, facilitating the speed of these tasks and thus obtaining a quality web system. The result was the development of an open-source web system focused on controlling food and physical health. This web system is designed responsively so that it can be used correctly from any device such as a laptop, tablet and/or cell phone, thus helping the user to visualize their progress in health control from any electronic device. In addition, this web system offers users attention via chat with the professionals in charge of their subscribed plan. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.
Keywords: Active methodologies; Innovative; Natural Sciences; Strategies; Teaching